CLINICAL SIGNIFICANCE OF ASPIRIN RESISTANCE IN PATIENTS WITH CARDIO-VASCULAR DISEASES - P. J. Dovgalevsky; N. V. Furman; N. F. Puchinian (Столичная издательская компания, 2016)
Atherothrombosis is a complication of ischemic heart disease, and it leads to development of acute coronary syndrome. Atherothrombosis is characterized by sudden destruction of atherosclerotic plaque, which results into platelets activation and thrombus formation. Aspirin - one of the most widely used antiaggregate drugs, prevents development of the recurring myocardium infarction, stroke, sudden coronary death. But in number of patients aspirin is not efficient. Development of repeated thrombotic complications with aspirin therapy or resistance to aspirin is independent predictor of high coronary risk. There are controversial data about aspirin resistance incidence, which varies from 5 to 48%. Possible reasons for this are discussed: low compliance with treatment, peculiarities of functional condition of platelets, genetically given variability of platelet receptors etc. Different methods, based on estimation of platelets activity are proposed to assess the possibility of repeated thrombotic complications, caused by resistance to aspirin. Further researches including valid number of patients are needed to assess incidence of aspirin resistance and to reveal mechanisms of its development.